THU0077 Interations between inflammatory polyarthritis and cardiovascular disease. (1st June 2001) - Dessein, PH; Stanwix, AE; Joffe, BI; Shipton, EA
Abstract : Background: Inflammatory polyarthritis (IP) and cardiovascular disease (CVD) may share a common predisposition and disease activity in IP may be complicated by worsening of CVD risk factors profiles. Objectives: The aim of the present study was to provide evidence for these hypotheses. Methods: A literature search on predisposing factors for IP and a case controlled study in 87 IP patients (38 rheumatoid arthritis, 29 spondyloarthropathy and 20 undifferentiated inflammatory arthritis) on CVD risk factors were performed. Results: Recently identified predisposing factors for IP bear remarkable similarities to CVD risk factors. They include ageing, obesity, smoking, elevated cholesterol and apolipoprotein (apo) (a) concentrations, subtle hypoadrenalism, decreased unsaturated fat intake and antioxidant concentrations, no alcohol intake, infections and stressful life events. Indeed, activation of nuclear factor kappa B, monoclonal expansion of proinflammatory CD4 + CD28- T cells and acute phase responses (APR), the mutually reinforcing relationship between obesity/insulin resistance (IR) and hypoadrenalism and, endothelial dysfunction may each play a pivotal role in both IP and CVD. In established IP, disease activity associates with the presence of APR, raised apo (a), cholesterol/HDL-cholesterol and apo B/A1 ratios, IR and decreased dehydroepiandrosterone sulphate (DHEAS) concentrations, thereby worsening CVD risk factor profiles. Three studies reported a 60–80% excess CVD mortality in rheumatoid arthritis. In a more recent investigation, in which disease modifying agents were instituted soon after disease onset, the 10 year survival was similar to the general population. In our controlled study, IP was associated with a positive family history for coronary artery disease (p < 0.03). Twenty five (29%) patients had IR and this could be accounted for by the APR and body mass index (BMI). Cholesterol/HDL-cholesterol ratios were elevated and this was only partially attributable to the APR, BMI and IR. Twenty four (28%) patients had decreased DHEAS concentrations and in women, this could not be fully explained by the APR, IR, disease duration, previous glucocorticoid and current NSAID usage. Conclusion: Further elucidation of etiopathogenetic mechanisms shared by IP and CVD may yield more effective therapies for both conditions. Meanwhile, CVD risk factor profiles should be addressed in IP management. References: Dessein PH, et al. Rheumatology 2001, in press Liuzzo G, et al. Circulation 2000;102: 2883–8 Weyand CM, et al. Arch Immunol Ther Exp (Warsz) 2000;48:429–35 Kroot EJ, et al . Ann Rheum Dis. 2000;59:954–8